2013 Cardiovascular Prevention Guidelines: A Discussion of the Good, the Bad, and the Ugly - Vinall, Maria (MD Conference Express, 2014)
Particular sections of the much anticipated 2013 American College of Cardiology (ACC)/American Heart Association (AHA) cardiovascular (CV) prevention guidelines have received both applause and criticism. This article presents experts' views on a few of the more divisive recommendations.